Luaran Klinik Terapi Antivirus pada Pasien Komorbid dan non-Komorbid T2-DM COVID-19 di RSUD Rasidin - Muslim Suardi (JURNAL FARMASI DAN MAKANAN, 2022)
Patients with comorbidity is vulnerable to being attacked by COVID-19. Diabetes mellitus comorbid patients have experience of higher severity viral infections than those without diabetes mellitus. The objective of the research was to evaluate the impact of Type 2 Diabetes Mellitus (T2-DM) comorbidity and antiviral therapy on the clinical outcome of COVID-19 patients. The study was performed following a cross sectional design from April 2020 to March 2021 at Hospital dr Rasidin Padang. Data were collected retrospectively from the patient's medical record. Treatment and clinical outcomes of patients were analyzed using the Kruskal Wallis, Mann-Withney U Test, Repeated Measured ANOVA, and Friedman Test. Results showed that the respiratory rate on T2-DM comorbid and non-comorbid patients were 20.58±0.25 and 20.15±0.08 times/minutes, respectively (p<0.05). While, oxygen saturation was 97.95±0.16 and 98.38±0.06%, respectively (p<0.05). Patient’s length of stay after the treatment of oseltamivir and favipiravir on non-comorbid COVID-19 patients were 14.76±0.861 and 9.96±0.488 days, respectively (p<0.01). While on comorbid patients were 16.00 ±3.17 and 10.47±0.77, respectively (p<0.01). Comorbidity had a significantly impacted on the patient's respiratory rate and oxygen saturation. The use of oseltamivir and favipiravir had a highly significant different on the LOS of comorbid and non-comorbid patients.